Biological diversity of epibenthic invertebrates in relation to environmental factors in lava caves around Lake Mývatn (N-E Iceland) - Combot, Doriane G. C. M., 1989- (2018)
Biodiversity, and its understanding and maintenance, are nowadays concerns in many fields of sciences. In freshwater, epibenthic invertebrates are important for their environment as consumers at intermediate trophic level and as food resources for other organisms. Their sensitivity to environmental conditions, influencing their biotic diversity and abundance, make them good indicators of the health of freshwater ecosystems. In the vicinity of Lake Mývatn (NE Iceland), numerous groundwater fed lava caves are found; they were formed after the collapse of lava tumuli. Groundwater seeps into the caves through porous lava bedrock, creating small ponds inhabited by Arctic charr and diverse invertebrates. The unique geomorphology of the caves creates various habitats, and along with that the potential for different invertebrate communities. In summer 2014, I sampled epibenthic crustaceans in 18 caves distributed in two areas around Lake Mývatn, Haganes and Vindbelgjar, along with measurements of environmental variables and geomorphology of the caves. I also sampled along a transect in four particular caves, to look at the changes in the diversity in relation to a light gradient. The main differences between Haganes and Vindbelgjar were observed with the environmental factors, which vary between the areas. Overall I found a low diversity of invertebrates in all lava caves although this diversity varied within and between areas. Some similarities in invertebrate composition were observed between the caves and the nearby Lake Mývatn. I found that the abundance of invertebrates per cave and per taxa decreased as light intensity decreased (i.e. going from the shore into the caves). Other than for light gradients, no clear correlations between environmental factors and invertebrate diversity was found. This study showed that even at small scale an ecosystem can be variable, and show differences. This is important for future studies and futures conservational ecology plans, not only for the caves, nor for Iceland, but ...